Evaluation of quizalofop-p-ethyl in cotton and effect on succeeding crop - Hooda, V. S.; Sangwan, Meenakshi; Singh, Samunder; Devi, Sudesh (Annals of Agricultural Research, 2018)
A field experiment was conducted during kharif season of 2013 and 2014 to evaluate the bio-efficacyand phytotoxicity of quizalofop-p-ethyl against weeds in cotton. During both the years of study,quizalofop-p-ethyl at 40, 50, 60 & 80 g/ha provided 27 to 60% control of weeds comparative topendimethalin used at 900 g/ha, however, lower dose of quizalofop-p-ethyl 30g/ha was very poorin controlling the weeds. At 50, 60 and 80 g/ha, quizalofop-p-ethyl did not caused any phytotoxicityin cotton crop and recorded a seed cotton yield which was at par among the treatments of quizalofopp-ethyl at 50, 60 & 80 g/ha which was significantly higher than rest of the treatments except weedfree situation. No residual toxicity on succeeding crop of wheat was observed by quizalofop-pethylapplication during two years of study.